1991
DOI: 10.1111/j.1432-1033.1991.tb16192.x
|View full text |Cite
|
Sign up to set email alerts
|

An intra‐dimeric crosslink of large subunits of spinach ribulose‐1,5‐bisphosphate carboxylase/oxygenase is formed by oxidation of cysteine 247

Abstract: Crystals of the hexadecameric form of ribulose-bisphosphate carboxylase used to solve the structure of the enzyme are composed of protein substantially crosslinked by a disulfide bond between pairs of large subunits. Conditions leading to the selective formation of dimers of the large subunits are described. The stability and specificity of the intra-dimeric crosslink was used to confirm that only one cysteine residue, Cys247 of neighboring large subunits, is involved in the bridge. The ability to generate thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
21
0

Year Published

1993
1993
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 17 publications
0
21
0
Order By: Relevance
“…The proximity of C172 to C192 (29) suggests that the two molecules may form an intramolecular disulfide bond. Furthermore, a disulfide bridge between Cys247 residues in the large subunit homodimer has been shown to be present after enzyme oxidation (30). Therefore, we examined the effect of replacement of Cys and whether the redox state affects the thermal stability of the enzyme by analyzing carboxylase activity after incubation at temperatures ranging from 5 to 100°C.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The proximity of C172 to C192 (29) suggests that the two molecules may form an intramolecular disulfide bond. Furthermore, a disulfide bridge between Cys247 residues in the large subunit homodimer has been shown to be present after enzyme oxidation (30). Therefore, we examined the effect of replacement of Cys and whether the redox state affects the thermal stability of the enzyme by analyzing carboxylase activity after incubation at temperatures ranging from 5 to 100°C.…”
Section: Resultsmentioning
confidence: 99%
“…The RuBisCO from cyanobacteria, algae (excluding some dinoflagellates), and higher plants is a hexadecamer consisting of eight large and eight small subunits organized as four protomers, each of which has two active sites at the interface between each large subunit pair (3,4,29). In the RuBisCO of many species, an intradimeric disulfide bond is formed under oxidizing conditions between the Cys247 residues of a large subunit pair (30). A sequence comparison of more than 500 RuBisCO genes revealed high levels of similarity, particularly among large subunits, and residues that form the catalytic site are entirely conserved (21).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This indicates that the increase in thermal sensitivity is due to DTT acting on disulfides other than the Cys-172/Cys-192 pair. Nonetheless, one may argue that the putative Cys-172-Cys-192 disulfide bond is resistant to DTT, as is the Cys-247-Cys-247 disulfide bond that is buried within the hydrophobic core of spinach Rubisco (7,44).…”
Section: Discussionmentioning
confidence: 99%
“…Although rubisco is not regulated this way (Campbell & Ogren, 1990), it is conceivable that the same regulatory mechanism causes disulfide links to be formed in the dark that are of no consequence for the catalytic activity. Ranty et al (1991) showed that the disulfide link present between dimer-related Cys 247 residues does not influence the catalytic activity. This disulfide link is present in the Data collection crystal structure ofspinach rubisco , Synechococcus rubisco (Newman & Gutteridge, 1990), and tobacco rubisco.…”
Section: Discussionmentioning
confidence: 99%